Analisys Of Product Quality, Price, And Promotion On Customer Satification In Micro, Small, And Medium Enterprises (Msmes) At The Aai Cen Batang Serangan - Nirmala, Patwa; Surya, Elfitra Dessy; Amelia, Ocdy (Journal of Management, Economic, and Accounting, 2025)
This study examines the impact of product quality, price, and promotion variables on customer satisfaction levels at the AAI Cen Batang Serangan MSME. The population consisted of 430 MSME customers, with a sample of 81 respondents selected through a simple random sampling technique. The study was conducted in 2025, using a questionnaire to obtain quantitative primary data, which were then analyzed with SPSS 24 through multiple linear regression. The analysis shows that product quality, price, and promotion individually and together have a significant positive effect on customer satisfaction. The partial test (t-test) revealed: product quality (regression 0.398, t-count 4.388, sig. 0.000); price (regression 0.331, t-count 3.858, sig. 0.000); promotion (regression 0.267, t-count 3.112, sig. 0.003). The simultaneous test (F test) produced an F-count of 222.143 (sig. 0.000), with a t-table of 1.991 and an F-table of 2.723, so all hypotheses (H1-H4) were accepted. Product quality was the dominant factor with the highest beta (0.351), explaining 89.2% of the variation in customer satisfaction, with a strong correlation (R = 0.947).